Teenage suicide notes: an ethnography of self-harm - Williams, Terry M. (The cosmopolitan life, 2017)
Prologue -- Introduction -- Little girl lost: Kyra -- The fighter: Enoch -- Overload: Candy -- The last stand: David -- Homo: Tucker -- Escaping death: Gita -- Shock jock: boots -- Cutter: Jill -- On the road: Cody -- Born-again virgin: Gabriella -- Afterword -- Epilogue -- Appendix 1: Ipe and Brownson -- Appendix 2: Enoch and his brother -- Notes -- Bibliography -- Index